SPECTRAL FLUCTUATION ANALYSIS REVEALS VARIATIONIN CICADA ADVERTISEMENT-SONG STRUCTURES - Quynh Hoa, Nguyen; Jang, Yikweon (HNUE Journal of Science: Journal of Natural Sciences, 2026)
Understanding song structure is a fundamental step in any bioacoustic study because it provides a basis for interpreting signal production and behavioral function. Previously, an analytical framework based on spectral fluctuation analysis of peak frequency and amplitude was proposed, considering peak frequency as a species-specific signal perceived by females. In this study, advertisement songs of three cicada species with varying structural complexity, Cryptotympana atrata, Graptopsaltria nigrofuscata, and Meimuna opalifera, were analyzed to evaluate the applicability of this framework. Spectral fluctuations were examined using the strucchange package in R, and generalized linear regression models were fitted between peak frequency and root-mean-square amplitude to identify structural breakpoints. The results showed that songs of C. atrata were primarily divided into two non-repetitive parts, whereas G. nigrofuscata produced songs comprising five distinct segments. In M. opalifera, advertisement songs consisted of five sequential parts, each containing multiple frequency- and amplitude-modulated echemes. These findings demonstrate the robustness of the proposed approach in identifying song structures across species with different levels of complexity and provide an informative foundation for subsequent bioacoustic and behavioral studies.